1980
DOI: 10.3109/00016358009003485
|View full text |Cite
|
Sign up to set email alerts
|

Sealing of preventively enlarged fissures

Abstract: The occlusal fissures of 156 permanent first molars in 63 children, 7--8 years of age, were sealed with a chemically polymerizing material (Delton). Deep and narrow fissures were opened up with a pointed diamond before etching and sealing. The treatment was performed by untrained dental students. The patients were called back for treatment every 6 months. 2/3 of the patients were followed up for a period of 2 1/2 years. After that period the retention of sealants was 93% (74 sealants) in ground deep fissures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This could be attributed to the penetration depth of the material into the fissure, smoothing of the cavity wall, and the absence of debris, which is more easily removed with the bur. Other studies have also shown that mechanical preparation of the fissure area reduces the risk of microleakage [10–13]. The results of this investigation demonstrated that microleakage of compomer was significantly higher in groups three and five (no acid etch) than groups two and six (acid etch).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This could be attributed to the penetration depth of the material into the fissure, smoothing of the cavity wall, and the absence of debris, which is more easily removed with the bur. Other studies have also shown that mechanical preparation of the fissure area reduces the risk of microleakage [10–13]. The results of this investigation demonstrated that microleakage of compomer was significantly higher in groups three and five (no acid etch) than groups two and six (acid etch).…”
Section: Discussionmentioning
confidence: 50%
“…These parameters appear to be of major importance for retention and longevity of the fissure sealing material [24]. For mechanical preparation, different types of burs such as a pointed diamond bur, a #1 round steel bur, and the Komet #8392 diamond bur have been used [8,11,13,15,24,25]. In this study, a #582 S diamond bur was used as significant advantages in the use of tapered fissure diamond burs over round burs have been reported [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air polishing, air abrasion, lasers and enameloplasty with a bur have all been trialled but all require further equipment, and change the enamel surface i.e., they are invasive. The change in retention is not significant enough to recommend them.…”
Section: Explanatory Notesmentioning
confidence: 96%